CONSTRUCTING VISUAL LEARNING STYLE STUDENTS’ READING COMPREHENSION USING METACOGNITIVE STRATEGY INSTRUCTIONS - Silvi Listia Dewi (Jurnal Pendidikan Almuslim, 2017)
Mainly, visual learners learn best using their eye sight. This type of learners tends to be fast talkers. They also tend to have a difficulty with verbal instruction. Seeing and reading are reflected to be important for visual learners, for example handouts, pictures, tables, demonstrations, and mind maps are very helpful for them. Considering that learning English includes learning to read written passages, this articlefinds out the possible strategy to assist them improve their reading achievement. This is critical because empirical evidence shows that visual learner is excellent in learning visually, especially using lecture notes, textbooks, pictures, films, text illustration, chart, diagram, and other written text is the most useful way of learning. The teacher can focus their attention appropriately in order to help visual learner achieve success in the classroom. Strategy use is fundamental to help determine how and how well learners learn a second/foreign language. To solve the problem, meta-cognitive strategies are believed to be the most suitable to help them learn to read better. This is because meta-cognitive strategies take care of how learners regulate their learning intentionally. As a result, this is the authority of the teacher to teach them to become regulators of their learning to read and use them to cope with different reading tasks selectively and appropriately in a more flexible way according to their need. So, metacognitive strategy instructions (MSI) can help learners use suitable strategy to make them strategic readers. As a result, being able to control over their reading process, EFL learners are expected to use these strategies as resources to pursue the goal of reading activities in English classes as a personal interpretation or meaning making rather than confining their experience or learning to an understanding or acquisition of English linguistic knowledge only. 27visual students were grouped by conducting VAK Questionnaire. Then, all subjects were administered the pre-test and after getting MSI training they got post reading comprehension test. The results showed that therewas no statistically significant higher between the pre and post-test mean reading score of the visual EFL Indonesian students after being taught using Metacognitive Strategy Instruction, because the significance value was (p = .731/2 = .3655) and it was far above the significance value α < .05. It expressed that visual learning style did not predispose the step-up of reading skill after being trained with Metacognitive Strategy Instruction. Keywords: Metacognitive Strategy Instruction, reading skill, visual learning style